THE EFFECT OF EDUCATIONAL GAME ON STRESS LEVEL OF PRE-SCHOOL CHILDREN AFTER KELUD MOUNTAIN DISASTER - . Adiyanto; . Muarrofah; . Baderi (Jurnal Keperawatan, 2011)
Childhood is golden period. Where pre school children experienced physical stress, emotions, thoughts and behaviors caused by various causes and sources such as disaster with concentration symptom, anxiety and fear. Pre-school children generally were cooperative in making game. The purpose of this study was to analyze the effect of educational game on stress level of pre-school children after Kelud mountain disaster.The design of this study used "Pre-experimental" (One Group Pre-Test - Post Test Design). In this study, the population was all pre-school children after disaster, amounting to 53 children and sample of this study was part of pre-school children after disaster in Dharma Wanita 5 kindergarten Kepung. Sampling technique used simple random sampling as many as 47 respondents.Variabel independent variable was influence of educative games and dependent variable was stress level on preschool children after Kelud mountain disaster. Data were collected by using questionnaires before and after provision of educational games. Data analysis used Wilcoxon test with number α = < 0,05. The study result showed that stress before being given educative game was severe category and after being given educative game was mild on the subject on significance level was p = 0,000 < 0,05.The conclusion H1 was accepted. It means no effect of educative game on the level of stress on pre-school children after the eruption of Kelud mountain. Based on the results of this study were expected the teacher can give educative game every week to students according with the standard curriculum of educative games that can be used as a reference in giving intervention on children to lose stress.